Failure mode and effect analysis in blood transfusion: a proactive tool to reduce risks. Issue 12 (8th April 2013) - Lu, Yao; Teng, Fang; Zhou, Jie; Wen, Aiqing; Bi, Yutian
<x xml:space="preserve">Abstract</x> Background The aim of blood transfusion risk management is to improve the quality of blood products and to assure patient safety. We utilize failure mode and effect analysis (FMEA), a tool employed for evaluating risks and identifying preventive measures to reduce the risks in blood transfusion. Study Design and Methods The failure modes and effects occurring throughout the whole process of blood transfusion were studied. Each failure mode was evaluated using three scores: severity of effect (S), likelihood of occurrence (O), and probability of detection (D). Risk priority numbers (RPNs) were calculated by multiplying the S, O, and D scores. The plan‐do‐check‐act cycle was also used for continuous improvement. Results Analysis has showed that failure modes with the highest RPNs, and therefore the greatest risk, were insufficient preoperative assessment of the blood product requirement (RPN, 245), preparation time before infusion of more than 30 minutes (RPN, 240), blood transfusion reaction occurring during the transfusion process (RPN, 224), blood plasma abuse (RPN, 180), and insufficient and/or incorrect clinical information on request form (RPN, 126). After implementation of preventative measures and reassessment, a reduction in RPN was detected with each risk. The failure mode with the second highest RPN, namely, preparation time before infusion of more than 30 minutes, was shown in detail to prove the efficiency of this tool. Conclusions FMEA evaluation model is a useful tool in proactively analyzing and reducing the risks associated with the blood transfusion procedure.